How Transition Paths Differ : Enterprise Performance in Russia and China - Sumon Kumar Bhaumik; Saul Estrin (Institute for the Study of Labor (IZA), 2005)
We use enterprise data to analyse and contrast the determinants of enterprise performance in China and Russia. We find that in China, enterprise growth and efficiency is associated with rapid increases in factor inputs, but not correlated with ownership or institutional factors. However, in Russia, enterprise growth is not associated with increases in factor quantity (except for labor) or quality. The main determinants of company performance are instead demand and institutional factors at a regional level. We explore possible interpretations of these results, including the impact of institutional and managerial quality.
Keywords: P31; O12; L22; D23; 330; enterprise performance; privatization in Russia and China; Systemtransformation; Privatisierung; Unternehmensentwicklung; Vergleich; China; Russland